Jack Stone in the Bladder: Is it Really a Rare Entity in Tropical Countries Like India - Dhangar, Dr. Sanjay P. (SP'z Series New Insights on Urology and Urological Research Part I, 2022)
Vesical calculus accounts for nearly 5% of urinary system calculus. Of these, jackstone constitutes a rare entity. Jackstones are stones that have a specific appearance resembling child’s toy. They consist of a dense central core and radiating spicules. Usually described in urinary bladder and rarely upper urinary tract, they are light brown with dark patches and an irregular shape. We here report multiple cases of jackstone from our hospital situated in hilly areas of Nashik district of Maharashtra, India and point out the possible reasons of their higher occurrence inspite of the rarity of the jackstone.